Composite powder for manufacturing porous body included in anode body of electrolytic capacitor, method of manufacturing the composite powder, and method of manufacturing anode body for electrolytic capacitor
The composite powder with aliphatic carboxylic acid compounds addresses the issue of high carbon content and mass variation in electrolytic capacitors, improving stability and reducing leakage current, thereby enhancing capacitor reliability.
Patent Information
- Application Number
- JP2023111402
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-20
AI Technical Summary
Existing methods for manufacturing electrolytic capacitors result in high carbon content from additives, leading to mass variation and increased leakage current, which affects the consistency and reliability of the capacitors.
A composite powder is used for manufacturing the anode body of electrolytic capacitors, comprising a raw material powder with an aliphatic carboxylic acid compound attached to the surface of the particles, which has a melting point of 35°C or higher, to improve weighing stability and reduce carbon content.
The use of aliphatic carboxylic acid compounds reduces carbon content and mass variation, enhancing the stability and reliability of the electrolytic capacitors by minimizing leakage current and improving production yield.
Smart Images

Figure 2025008844000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composite powder used to manufacture a porous body contained in an anode body of an electrolytic capacitor, a method for manufacturing the composite powder, and a method for manufacturing an anode body for an electrolytic capacitor. [Background technology]
[0002] In recent years, electrolytic capacitors with small equivalent series resistance (ESR) and excellent frequency characteristics have been developed. The anode body of the electrolytic capacitor includes, for example, a porous body containing a valve metal and a dielectric layer covering the porous body. The raw material for the porous body is, for example, raw material powder containing a valve metal to which an additive (binder) is added.
[0003] Patent Document 1 proposes a "solid electrolytic capacitor including a capacitor element including a sintered porous anode body; a dielectric disposed on the anode body; and a solid electrolyte disposed on the dielectric body, the solid electrolyte including a conductive polymer and a depolarizer." Patent Document 1 also lists a powder containing tantalum as an example of a powder used to form the sintered porous anode body. Patent Document 1 lists sodium polyacrylate, stearic acid, and the like as specific examples of binders used to aggregate powder particles.
[0004] In Patent Document 2, "a tantalum powder containing tantalum, hydrogen doped in the tantalum, and nitrogen doped in the tantalum is described, and the hydrogen (H) content (ppm) of the tantalum powder is calculated based on the Brunauer-Emmett-Teller (BET) surface area (m 2 The tantalum powder has a hydrogen content of 300 ppm to 1200 ppm, a nitrogen content of 500 ppm to 3,500 ppm, and a hydrogen content of 300 ppm to 1,200 ppm. 2 / g~about 10m 2 / g」。 Furthermore, in Patent Document 2, camphor, stearic acid, etc. are given as specific examples of binders to be added to the tantalum powder.
[0005] Patent Document 3 proposes "a method for making an anode for an electrolytic capacitor, the method comprising the steps of combining a metal powder and an effective amount of dimethyl sulfone as a binder; pressing the powder and dimethyl sulfone to form an anode body; and removing the dimethyl sulfone."
[0006] Patent Document 4 proposes "a method for sintering a tantalum capacitor anode element, characterized in that a tantalum anode element obtained by compression molding tantalum powder mixed with an adhesive is placed in a drying furnace filled with a degreasing solvent, and subjected to sealed low-temperature solvent catalytic wet dewaxing, followed by vacuum drying and further vacuum sintering." Patent Document 4 lists camphor, benzoic acid, stearic acid, etc. as specific examples of adhesives.
[0007] Patent Document 5 proposes a method for manufacturing an element for a solid electrolytic capacitor, which comprises pressure-molding a valve action metal powder containing a binder to obtain a molded element, and then sintering the molded element in a vacuum, characterized in that the molded element is immersed in pure water and subjected to ultrasonic vibration. Patent Document 5 lists stearic acid, palmitic acid, and benzoic acid as specific examples of binders. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Special Publication No. 2022-533161 [Patent Document 2] Special Publication No. 2020-500260 [Patent Document 3] Special Publication No. 2003-509583 [Patent Document 4] JP 2013-135211 A [Patent Document 5] JP 2007-273710 A Summary of the Invention [Problem to be solved by the invention]
[0009] There is a demand for a porous body contained in an anode body of an electrolytic capacitor to have a reduced carbon content derived from additives that are added to raw material powder containing a valve metal during the porous body production process, and to have a reduced mass variation. [Means for solving the problem]
[0010] One aspect of the present disclosure relates to a composite powder used for manufacturing a porous body included in an anode body of an electrolytic capacitor, the composite powder including a raw material powder containing a valve action metal and an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and polymers) adhered to surfaces of particles of the raw material powder, and the aliphatic carboxylic acid compound has a melting point of 35° C. or higher.
[0011] Another aspect of the present disclosure relates to a method for producing a composite powder used in producing a porous body included in an anode body of an electrolytic capacitor, the method including the steps of: preparing a raw material powder containing a valve action metal; preparing a carboxylic acid solution containing an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and a polymer) having a melting point of 35°C or higher and a solvent; adding the carboxylic acid solution to the raw material powder while stirring the raw material powder to obtain a wet raw material powder; and removing the solvent by drying the wet raw material powder while stirring to obtain a composite powder.
[0012] Yet another aspect of the present disclosure relates to a method for producing an anode body for an electrolytic capacitor, the method including the steps of: preparing a composite powder including a raw material powder containing a valve action metal and an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and polymers) adhered to surfaces of particles of the raw material powder; filling the composite powder into a predetermined molding die and pressure-molding it to obtain a molded body; removing the aliphatic carboxylic acid compound contained in the molded body; sintering the molded body from which the aliphatic carboxylic acid compound has been removed to obtain a porous body; and forming a dielectric layer on a surface of the porous body to obtain an anode body, wherein the melting point of the aliphatic carboxylic acid compound is 35° C. or higher. Effect of the Invention
[0013] According to the present disclosure, for a porous body included in an anode body of an electrolytic capacitor, it is possible to reduce the carbon content derived from additives added to raw material powder containing a valve metal during the production process of the porous body, and to reduce mass variation. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a diagram showing an example of wet mixing of a raw material powder and an aliphatic carboxylic acid compound A. [Diagram 2] 2 is a diagram showing an example of a process for producing a compact from a composite powder, in which (a) shows the state of the composite powder when it is weighed, (b) shows the state of the composite powder before compression molding, and (c) shows the state of the composite powder during compression molding. [Diagram 3] FIG. 2 is a configuration diagram showing an example of equipment used in a step of removing an aliphatic carboxylic acid compound A and a step of sintering a molded body. [Figure 4] 1 is a cross-sectional view illustrating a schematic diagram of an electrolytic capacitor according to an embodiment of the present disclosure. [Diagram 5] FIG. 11 is a cross-sectional view showing a state in which a powder is filled in a jig set for evaluating weighing stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In the following, the embodiment of the present disclosure will be described by way of example, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and materials may be applied as long as the effects of the present disclosure are obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "numerical value A or more and numerical value B or less." In the following description, when a lower limit and an upper limit are exemplified for numerical values of specific physical properties or conditions, any of the exemplified lower limits and any of the exemplified upper limits can be arbitrarily combined as long as the lower limit is not equal to or greater than the upper limit. When multiple materials are exemplified, one of them may be selected and used alone, or two or more may be used in combination.
[0016] The anode body of the electrolytic capacitor includes a porous body (porous sintered body) containing a valve metal, and a dielectric layer covering the surface of the porous body. The present disclosure relates to a composite powder used to manufacture the porous body contained in the anode body of the electrolytic capacitor. The composite powder according to the embodiment of the present disclosure includes a raw material powder containing a valve metal, and an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and polymers) attached to the surface of the particles of the raw material powder. The melting point of the aliphatic carboxylic acid compound is 35°C or higher.
[0017] Hereinafter, aliphatic carboxylic acid compounds (excluding stearic acid, palmitic acid, and polymers) having a melting point of 35°C or higher are also referred to as "aliphatic carboxylic acid compound A". Raw material powder particles are also referred to as "raw material particles". Composite powder particles have raw material particles and aliphatic carboxylic acid compound A attached to the surfaces of the raw material particles. Hereinafter, composite powder particles are also referred to as "composite particles".
[0018] In the composite powder in which an aliphatic carboxylic acid compound A is added as an additive to the raw material powder, the weighing stability (fluidity) can be improved. This can reduce the mass variation of the compact or porous body (anode body). Furthermore, in the case of the aliphatic carboxylic acid compound A, the weighing stability can be sufficiently improved by adding a small amount, and the carbon content derived from the additive in the porous body can be reduced, and the increase in leakage current when the carbon content is high can be suppressed.
[0019] In addition, the high weighing stability of the powder means that when the powder is weighed by filling the weighing hole of the weighing jig with the powder using a leveling jig, the variation in the amount of the powder filled into the weighing hole is small. The powder is weighed, for example, by filling the powder 300 into the weighing hole 420a in FIG. 2(a).
[0020] If the mass variation of the porous bodies is large, the surface area of the porous bodies (anode bodies) will vary greatly, which may increase the variation in the capacitance of the electrolytic capacitor. In addition, in the above case, when multiple porous bodies are subjected to a chemical conversion treatment at the same chemical conversion voltage at the same time, the chemical conversion current varies greatly between the porous bodies, which increases the variation in the film quality of the formed chemical conversion film, which may increase the variation in the leakage current (LC) of the electrolytic capacitor. In this way, the variation in the characteristics of the electrolytic capacitor may increase. One method for reducing the variation in the characteristics of the electrolytic capacitor is to remove those that are outside a predetermined mass range as defective products at the stage of obtaining the molded body, but in the above case, the molding defect rate increases, which is disadvantageous in terms of productivity.
[0021] (Raw material powder) The raw material powder contains a valve metal. Examples of the valve metal include aluminum (Al), titanium (Ti), tantalum (Ta), niobium (Nb), zirconium (Zr), and hafnium (Hf). The raw material particles may be particles of a valve metal, particles of an alloy containing a valve metal, or particles of a compound containing a valve metal. Only one type of particle may be used, or two or more types may be mixed together.
[0022] The average particle size of the raw material powder may be 100 μm or less, or may be 80 μm or less. In this case, the increase in density variation of the molded body due to uneven distribution of coarse particles in part of the molded body can be suppressed, and the flatness of the surface of the molded body can be improved, thereby reducing the dimensional variation of the molded body. In addition, since it is relatively difficult to make the average particle size of 100 μm or more in powders with a CV value of 100 μFV / g (100 kCV) or more, there is also an advantage that the options when selecting raw material powders are expanded. By adding the aliphatic carboxylic acid compound A, the weighing stability of the raw material powder with an average particle size of 100 μm or less can be improved. If camphor is added to a raw material powder with an average particle size of 100 μm or less, the weighing stability of the powder may be reduced.
[0023] In addition, from the viewpoint of suppressing the powder from floating up into the air, the average particle size of the raw material powder may be 10 μm or more. In this case, the powder loss due to the powder floating up into the air when transferring from one container to another can be suppressed, and the risk of workers inhaling the powder can be reduced. In addition, the small particle size can also suppress the scattering of particles from the gaps in the molded parts.
[0024] The average particle size referred to here is the median diameter (D50) in the volume particle size distribution determined by a laser diffraction type particle size distribution measuring device.
[0025] (Aliphatic carboxylic acid compound A) The aliphatic carboxylic acid compound A has a melting point of 35°C or higher and is stable in a solid state at room temperature (about 20 to 25°C). Therefore, the composite powder can be obtained as a dry powder, and excellent flowability can be ensured. The melting point of the aliphatic carboxylic acid compound A may be 40°C or higher, or 45°C or higher.
[0026] From the viewpoint of productivity in the step of removing the aliphatic carboxylic acid compound A described later, the melting point of the aliphatic carboxylic acid compound A is preferably 120°C or less, more preferably 100°C or less, even more preferably 90°C or less, and particularly preferably 80°C or less. When the melting point of the aliphatic carboxylic acid compound A is in the above range, in the step of removing the aliphatic carboxylic acid compound A using the equipment of FIG. 3, the adhesion of the aliphatic carboxylic acid compound A to the inner wall of the pipe can be suppressed by maintaining the temperature of the pipe (heat-insulating pipe 540 in FIG. 3) from the removal furnace of the aliphatic carboxylic acid compound A to the recovery tank at about 120 to 150°C. In addition, there is no need to install a pipe with a heat-resistant structure or to add equipment for heating the pipe to 150°C or more, which is advantageous in terms of cost. If the additive is benzoic acid (melting point 122.4°C), when the temperature of the above-mentioned piping is within the range of about 120 to 150°C, benzoic acid may precipitate inside the piping (or near the piping in the removal furnace).
[0027] The boiling point of the aliphatic carboxylic acid compound A is preferably 400° C. or lower. In the step of removing the aliphatic carboxylic acid compound A, the aliphatic carboxylic acid compound A can be removed by evaporation at a temperature of 400 to 500° C. This temperature range is almost the same as the temperature range for removing camphor by evaporation and the temperature range for removing acrylic resin by thermal decomposition and evaporation, and the equipment used when camphor or acrylic resin was used as an additive can be used as is.
[0028] The aliphatic carboxylic acid compound A does not include a polymer. Examples of the polymer include polyacrylic acid and its Na salt. In the case of a polymer, the amount of the polymer added to the raw powder is increased to improve weighing stability, and the carbon content of the porous body may be increased. When a composite powder is obtained using a polymer, the polymer is likely to form agglomerates (e.g., 300 μm or more) of particles that are tightly adhered to each other after the solvent removal process. The agglomerates are likely to cause problems such as increased variation in the filling of the powder into the weighing hole, localized dense parts being formed inside the molded body, and the formation of a sintered body with an irregular shape. Therefore, a separate process for removing the agglomerates is required, which leads to loss of powder and is disadvantageous in terms of productivity. Moreover, polyacrylic acid is not preferable from the viewpoint of its harmfulness to the human body, etc. Furthermore, its Na salt is not preferable because Na may be mixed into the porous body as a metal impurity, which may lead to a decrease in reliability such as an increase in LC.
[0029] The aliphatic carboxylic acid compound A does not include stearic acid and palmitic acid. Stearic acid is difficult to dissolve in a solvent (such as ethanol, which will be described later), and it takes time to dissolve. In addition, due to its low solubility, when mixing the raw material powder with a liquid containing stearic acid, even a small amount of evaporation of the solvent causes stearic acid to precipitate, which tends to cause uneven mixing, making it unsuitable for wet mixing with the raw material powder. The same can be said for palmitic acid.
[0030] The number of carbon atoms in the aliphatic carboxylic acid compound A is, for example, 12 or more in the case of a saturated fatty acid, and, for example, 3 or more in the case of an unsaturated fatty acid. The aliphatic carboxylic acid compound A may be used alone or in combination of two or more.
[0031] The aliphatic carboxylic acid compound A may be a saturated fatty acid. Examples of the saturated fatty acid include lauric acid, tridecylic acid, myristic acid, and pentadecylic acid. These compounds have a high solubility of 20 g or more per 100 g of ethanol or the like described below, a melting point within the range of 35 to 100°C, and a boiling point of 400°C or less.
[0032] The aliphatic carboxylic acid compound A may be an unsaturated fatty acid. Examples of the unsaturated fatty acid include crotonic acid, elaidic acid, vaccenic acid, nervonic acid, eleostearic acid, etc. These compounds are easily soluble in ethanol, etc., as described below, and have a melting point in the range of 35 to 120°C and a boiling point of 400°C or less.
[0033] The aliphatic carboxylic acid compound A may be a monocarboxylic acid or a dicarboxylic acid. Examples of the monocarboxylic acid include those exemplified above. Examples of the dicarboxylic acid include glutaric acid. Glutaric acid is easily dissolved in ethanol, etc., described later, and has a melting point in the range of 35 to 120°C and a boiling point of 400°C or less.
[0034] The content of the aliphatic carboxylic acid compound A in the composite powder is preferably 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder. When the content of the aliphatic carboxylic acid compound A is 0.1 parts by mass or less, the carbon content of the porous body is sufficiently reduced, and the leakage current is sufficiently reduced. In addition, the strength of the molded body is sufficiently ensured. When the content of the aliphatic carboxylic acid compound A is 0.002 parts by mass or more, the weighing stability of the composite powder is easily improved. From the viewpoint of further reducing the carbon content of the porous body, the content of the aliphatic carboxylic acid compound A is more preferably 0.002 parts by mass or more and 0.05 parts by mass or less. In addition, from the viewpoint of further improving the weighing stability of the powder, the content of the aliphatic carboxylic acid compound A is more preferably 0.005 parts by mass or more and 0.1 parts by mass or less. The content of the aliphatic carboxylic acid compound A is particularly preferably 0.005 parts by mass or more and 0.05 parts by mass or less.
[0035] If the additive is an acrylic polymer, the carbon content of the porous body increases, and the leakage current (LC) may increase. Although the detailed reason is unclear, it is assumed that a large amount of acrylic polymer must be added to improve weighing stability (for example, 1 part by mass or more of acrylic polymer is added to 100 parts by mass of raw material powder), and some of the pyrolysis products generated by pyrolysis in the additive removal process tend to remain without being removed by evaporation. Examples of acrylic polymers include poly(meth)acrylic acid and its salts, and polymers of (meth)acrylic acid esters (acrylic resins). "(Meth)acrylic acid" means at least one selected from the group consisting of "acrylic acid" and "methacrylic acid".
[0036] The content of the additive (aliphatic carboxylic acid compound A) in the composite powder (amount per 100 parts by mass of raw material powder) can be determined as follows. The composite powder is placed in an organic solvent such as ethanol, stirred, and then the raw material powder (e.g., Ta powder) and the liquid (carboxylic acid solution) are separated by filtration, centrifugation, or the like. The liquid is dried to obtain a precipitate (additive). The masses of the raw material powder and the precipitate are measured, and the mass ratio (percentage) of the precipitate to the raw material powder is determined.
[0037] The components of the additives can be determined, for example, by gas chromatography mass spectrometry. The melting point and boiling point are measured by a general method described, for example, in the Japanese Industrial Standards (JIS). If necessary, the melting point may be measured by differential scanning calorimetry (DSC). If necessary, the boiling point may be measured by thermogravimetry / differential thermal analysis (TG / DTA).
[0038] [Method of manufacturing composite powder] A manufacturing method of a composite powder according to an embodiment of the present disclosure includes a step of preparing a raw material powder containing a valve action metal, a step of preparing a solution of an aliphatic carboxylic acid compound A (hereinafter also referred to as "carboxylic acid solution A"), a step of mixing the raw material powder with the carboxylic acid solution A, and a step of removing the solvent.
[0039] When a small amount (for example, 0.1 parts by mass or less) of the aliphatic carboxylic acid compound A is added to 100 parts by mass of the raw powder, the aliphatic carboxylic acid compound A is dissolved in a solvent and mixed with the raw powder to produce a wet raw powder (wet mixing), thereby producing a homogeneous composite powder. If a small amount of the aliphatic carboxylic acid compound A is dry mixed with the raw powder at a temperature equal to or higher than the melting point of the aliphatic carboxylic acid compound A, it is difficult to spread the small amount of molten aliphatic carboxylic acid compound A over the entire surface of the raw powder, making it difficult to produce a homogeneous composite powder. In addition, in this method, the molten aliphatic carboxylic acid compound A is likely to adhere to the wall of the mixing container, and the proportion that does not contribute to the compounding may increase, making it difficult to adjust the amount of the aliphatic carboxylic acid compound A added to the raw powder.
[0040] (Raw powder preparation process) The raw material powder may be any of those exemplified above.
[0041] (Preparation of Carboxylic Acid Solution A) The carboxylic acid solution A includes an aliphatic carboxylic acid compound A and a solvent. The aliphatic carboxylic acid compound A may be one exemplified above. The concentration of the aliphatic carboxylic acid compound A in the carboxylic acid solution is, for example, 0.01 to 2% by mass. The concentration of the aliphatic carboxylic acid compound A in the carboxylic acid solution can be calculated from the content of the aliphatic carboxylic acid compound A in the composite powder and the amount of the carboxylic acid solution A added in the manufacturing process. When it is necessary to lower the concentration of the carboxylic acid solution A, a high-concentration carboxylic acid solution A may be prepared first, and then the solution may be diluted with a solvent to lower the concentration. For example, a 1% by mass carboxylic acid solution A may be prepared, and then a 0.1% by mass carboxylic acid solution A may be prepared by mixing the 1% by mass carboxylic acid solution A and the solvent in a mass ratio of 1:9.
[0042] The solvent is preferably a solvent that is relatively less harmful than a highly harmful solvent such as toluene. Examples of the solvent that is relatively less harmful include ethanol, isopropanol, and butyl acetate (hereinafter also referred to as "ethanol, etc."). The solvent may be used alone or in combination of two or more kinds.
[0043] The solvent is preferably ethanol, isopropanol, or butyl acetate, and the solubility of the aliphatic carboxylic acid compound A in 100 g of the solvent at 20° C. is preferably 20 g or more. It is preferable that the solubility is within the above range in at least one of the three solvents. In this case, the dissolution rate of the aliphatic carboxylic acid compound A in the solvent is fast, and the carboxylic acid solution A can be easily prepared. In this case, the occurrence of uneven mixing is sufficiently suppressed, and the raw material particles and the aliphatic carboxylic acid compound A can be easily mixed homogeneously.
[0044] If the additive has low solubility in the solvent, it takes a long time to prepare the additive solution, and the solvent evaporates when the additive solution and the raw powder are mixed, causing some of the additive to precipitate on the wall of the mixing tank, resulting in uneven mixing. If the additive is stearic acid, stearic acid has low solubility in ethanol, etc., so it takes a long time to prepare a stearic acid solution using ethanol, etc., and when the stearic acid solution and the raw powder are mixed, a white solid substance is likely to adhere to the wall of the mixing tank, resulting in uneven mixing. The same can be said if the additive is palmitic acid.
[0045] (Mixing process of raw material powder and carboxylic acid solution A) This step is a step of wet-mixing the raw material powder with the aliphatic carboxylic acid compound A. That is, in the mixing step, a carboxylic acid solution is added to the raw material powder while stirring the raw material powder, thereby obtaining a wet raw material powder.
[0046] The amount of the aliphatic carboxylic acid compound A added is preferably 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder. When the amount of the aliphatic carboxylic acid compound A added is 0.1 parts by mass or less, the carbon content of the porous body is sufficiently reduced, and the strength of the molded body is sufficiently ensured, and the occurrence of cracks or partial defects in the sintered body due to a decrease in strength is sufficiently suppressed. When the amount of the aliphatic carboxylic acid compound A added is 0.002 parts by mass or more, a composite powder with excellent weighing stability is easily obtained.
[0047] From the viewpoint of sufficiently suppressing the occurrence of uneven mixing and easily obtaining a homogeneous composite powder, the amount of carboxylic acid solution A added is preferably 5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of raw material powder. When the amount of carboxylic acid solution A added is within the above range, it is easy to adjust the entire raw material powder to a moderately wet state. When the amount of carboxylic acid solution A added is small, it may be difficult for the aliphatic carboxylic acid compound A to spread uniformly throughout the entire raw material powder. When the amount of carboxylic acid solution A added is large, the raw material powder becomes a slurry state, and a large amount of the carboxylic acid solution A and raw material powder may adhere to the wall of the mixing container, and a large amount of the aliphatic carboxylic acid compound A may precipitate on the wall of the mixing container during drying (solvent removal process).
[0048] (Solvent removal process) In the solvent removal step, the wet raw material powder is dried while being stirred to remove the solvent, thereby obtaining a composite powder. The composite powder contains the raw material powder and the aliphatic carboxylic acid compound attached to the surface of the raw material powder particles. Drying can be performed by heating, reducing pressure, etc. When the solvent is ethanol, drying can be performed by heating at about 50 to 90°C.
[0049] When the heat drying is performed, it is preferable to maintain the stirring state until the temperature of the raw material powder falls below the melting point of the aliphatic carboxylic acid compound A. If the stirring is stopped before the temperature of the raw material powder falls below the melting point of the aliphatic carboxylic acid compound A, the molten aliphatic carboxylic acid compound A may move, causing uneven mixing.
[0050] Here, Fig. 1 is a diagram showing an example of wet mixing of raw material powder and aliphatic carboxylic acid compound A. Raw material powder 100 is placed in a mixing container 110. A solution 200 of aliphatic carboxylic acid compound A is added to raw material powder 100 while stirring raw material powder 100. In this manner, raw material powder 100 in a wet state is obtained. Thereafter, the wet raw material powder 100 placed in the mixing container 110 is dried while being stirred to remove the solvent. In this manner, a composite powder is obtained.
[0051] [Method of manufacturing an anode body for electrolytic capacitors] The anode body for an electrolytic capacitor according to an embodiment of the present disclosure includes a step of preparing a composite powder, a step of molding the composite powder, a step of removing the aliphatic carboxylic acid compound A, a step of sintering the molded body, and a step of forming a dielectric layer.
[0052] (Composite powder preparation process) In this step, the composite powder of the present disclosure is prepared. In this step, for example, the composite powder obtained by the above-mentioned manufacturing method is prepared.
[0053] (Composite powder molding process) In the molding step of the composite powder, the composite powder is filled into a predetermined molding die and pressure molded to obtain a molded body. This molded body contains an aliphatic carboxylic acid compound A. In this step, a part of the anode wire may be embedded in the molded body.
[0054] FIG. 2 is a diagram showing an example of a process for producing a compact from a composite powder. First, as shown in FIG. 2(a), the composite powder 300 is put into a weighing hole 420a having a certain volume formed by a weighing mold 420 and a lower mold 440, and the weighing hole 420a is filled with the composite powder 300 using a leveling slider 410. In this manner, the composite powder 300 is weighed. At this time, since the composite powder 300 containing the aliphatic carboxylic acid compound A has excellent weighing stability, the weighing can be stably performed by filling the weighing hole 420a with the powder 300 using the leveling slider 410. That is, the variation in the amount of powder filled into the weighing hole 420a can be reduced. This can reduce the mass variation in each of the molded body, the porous body, and the sintered body produced in the subsequent process.
[0055] 2(b), the weighed composite powder 300 is placed in a predetermined space 460 formed by a pressing die 430 and a lower die 440. After that, an upper die 450 is placed above the space 460, and the anode wire 6 is inserted into a predetermined hole of the upper die 450 so that a part of the anode wire 6 is placed in the space 460. 2(c), the pressing die 430 is moved in the direction of the arrow to pressure-mold the composite powder 300. In this manner, a compact 310 in which a part of the anode wire 6 is embedded is formed.
[0056] (Step of Removing Aliphatic Carboxylic Acid Compound A) In the step of removing the aliphatic carboxylic acid compound A, the aliphatic carboxylic acid compound A contained in the molded body is removed. For example, the aliphatic carboxylic acid compound A contained in the molded body can be removed by vaporizing it. More specifically, the removal can be performed, for example, by heating the molded body to a predetermined temperature (a temperature equal to or higher than the boiling point of the aliphatic carboxylic acid compound A) under reduced pressure. When the boiling point of the aliphatic carboxylic acid compound A is 400°C or lower, the aliphatic carboxylic acid compound A can be removed at a temperature of about 400 to 500°C under reduced pressure. The reduced pressure in the removal step may be under vacuum, or may be under an atmosphere in which a small amount of inert gas such as Ar gas is introduced while performing evacuation by a vacuum pump.
[0057] In the case of the aliphatic carboxylic acid compound A, the weighing stability of the powder can be sufficiently increased by adding a small amount of the compound, so that the amount of the compound A remaining in the molded body without being removed in the removing step can be sufficiently reduced. As a result, the carbon content derived from the compound A in the sintered body obtained in the subsequent step can be sufficiently reduced.
[0058] (Sintering process of compact) In the sintering process of the molded body, the molded body from which the aliphatic carboxylic acid compound A has been removed is sintered to obtain a porous body (sintered body). Details of the porous body will be described later. The molded body can be sintered, for example, under reduced pressure at a temperature of 1200 to 1500°C. The reduced pressure in the sintering process is preferably under high vacuum.
[0059] Fig. 3 is a configuration diagram showing an example of equipment used in the process of removing the aliphatic carboxylic acid compound A and the process of sintering the molded body. In Fig. 3, molded body A is a molded body containing the aliphatic carboxylic acid compound A, and molded body B is a molded body after the treatment of removing the aliphatic carboxylic acid compound A has been performed.
[0060] The equipment 500 includes a removal furnace 510 for removing the aliphatic carboxylic acid compound A from the molded body A to obtain a molded body B, a sintering furnace 520 for sintering the molded body B, a recovery tank 530 for recovering the aliphatic carboxylic acid compound A removed from the molded body A, a heat-insulating pipe 540, and a vacuum pump 550. The heat-insulating pipe 540 is disposed between the removal furnace 510 and the recovery tank 530.
[0061] The temperature inside the heat-insulating pipe 540 is adjusted to a temperature equal to or higher than the melting point of the aliphatic carboxylic acid compound A. This suppresses precipitation of the aliphatic carboxylic acid compound A inside the pipe 540. For example, when the melting point of the aliphatic carboxylic acid compound A is 100° C. or lower, the temperature inside the pipe 540 may be maintained at about 120 to 150° C. In this case, there is no need to provide a pipe with a special heat-insulating structure, which is advantageous in terms of manufacturing costs.
[0062] Between the removal furnace 510 and the vacuum pump 550, the heat-retaining pipe 540 and the recovery tank 530 are arranged. The insides of the removal furnace 510, the heat-retaining pipe 540, and the recovery tank 530 are depressurized by the vacuum pump 550. The inside of the sintering furnace 520 is also depressurized by the vacuum pump 550. The recovery tank 530 is cooled with liquid nitrogen or the like, and the aliphatic carboxylic acid compound A is solidified and recovered. Valves may be provided between the removal furnace 510 and the sintering furnace 520, between the removal furnace 510 and the heat-retaining pipe 540, between the heat-retaining pipe 540 and the recovery tank 530, between the recovery tank 530 and the vacuum pump 550, and between the sintering furnace 520 and the vacuum pump 550. The valves may be opened and closed depending on the location and timing where depressurization is required.
[0063] The removing step and the sintering step using the apparatus of FIG. 3 will be described below. The compact A is supplied to a removal furnace 510 under reduced pressure, where the aliphatic carboxylic acid compound A is removed from the compact A, thereby producing a compact B. Next, the compact B is supplied to a sintering furnace 520 under reduced pressure and sintered, thereby producing a sintered body. Meanwhile, the aliphatic carboxylic acid compound A removed by evaporation in the removal furnace 510 passes through a heat-insulating pipe 540 and is recovered in a recovery tank 530.
[0064] In FIG. 3, the removal furnace and the sintering furnace are provided separately, but a single furnace may be provided that functions as both a removal furnace and a sintering furnace. That is, the removal step and the sintering step may be performed in a single furnace. The removal furnace and / or the sintering furnace may be configured as a single furnace or as a plurality of furnaces. As for the vacuum pump, a vacuum pump connected to the collection tank and a vacuum pump connected to the sintering furnace may be provided separately.
[0065] (Dielectric layer forming process) In the dielectric layer forming step, a dielectric layer is formed on the surface of the porous body to obtain an anode body. The dielectric layer is formed, for example, by chemical conversion treatment. The details of the dielectric layer will be described later.
[0066] The electrolytic capacitor will be described in detail below.
[0067] [Electrolytic capacitor] The electrolytic capacitor includes a capacitor element. The capacitor element includes an anode body and a cathode portion. The anode body includes a porous body and a dielectric layer covering a surface of the porous body. The cathode portion is formed so as to cover the dielectric layer. The cathode portion includes at least a solid electrolyte layer.
[0068] The anode body may include a rod-shaped anode wire partly embedded in the porous body. When the porous body is a rectangular parallelepiped, the anode wire is planted from one end face of the rectangular parallelepiped. The anode wire may include a valve metal. A part of the anode wire is embedded in the porous body, and the remainder protrudes from the porous body. The remainder is connected to an anode lead terminal by welding or the like.
[0069] (Porous body) The porous body contains a valve metal, such as aluminum (Al), titanium (Ti), tantalum (Ta), niobium (Nb), zirconium (Zr), or hafnium (Hf).
[0070] The porous body is a sintered product of a compact of raw material particles (raw material powder) containing a valve metal. The particles may be particles of a valve metal, particles of an alloy containing a valve metal, or particles of a compound containing a valve metal. The particles may be of one type or a mixture of two or more types.
[0071] The porous body can be obtained by pressurizing raw material particles into a predetermined shape to obtain a molded body, and then sintering the molded body. For example, an anode wire may be placed at a predetermined position in a mold, raw material particles may be charged into the mold, and the molded body may be pressurized to obtain a molded body. The molded body may be sintered to obtain a porous body in which a part of the anode wire is embedded. The porous body is usually a rectangular parallelepiped.
[0072] (Dielectric layer) The dielectric layer is formed so as to cover the outer surface of the porous body and the inner wall surface of the pores of the porous body. The dielectric layer is formed, for example, by subjecting the porous body to a chemical conversion treatment and growing an oxide film on the surface of the porous body. The chemical conversion treatment may be performed by immersing the porous body in a chemical conversion solution to anodize the surface of the porous body. Alternatively, the surface of the porous body may be oxidized by heating the porous body in an atmosphere containing oxygen.
[0073] (Solid electrolyte layer) The solid electrolyte layer is disposed so as to cover at least a part of the dielectric layer. The solid electrolyte layer may be filled in the pores of the porous body via the dielectric layer and formed on the outer surface of the porous body. The solid electrolyte layer may be a laminate of two or more different solid electrolyte layers.
[0074] The solid electrolyte layer includes a conductive polymer. The conductive polymer may be a π-conjugated polymer, and examples of the conductive polymer include polypyrrole, polythiophene, polyaniline, and derivatives thereof. These may be used alone or in combination. The conductive polymer may be a copolymer of two or more monomers. The derivative of a conductive polymer means a polymer having a conductive polymer as a basic skeleton. For example, an example of a derivative of polythiophene includes poly(3,4-ethylenedioxythiophene) (PEDOT).
[0075] A dopant may be added to the conductive polymer. That is, the solid electrolyte layer may include a conductive polymer and a dopant. The conductive polymer may be included in the solid electrolyte layer in a state where the dopant is doped. The dopant may be selected according to the conductive polymer, and a known dopant may be used. Examples of the dopant include benzenesulfonic acid, alkylbenzenesulfonic acid, naphthalenesulfonic acid, alkylnaphthalenesulfonic acid, polystyrenesulfonic acid (PSS), and salts thereof. The solid electrolyte layer may include, for example, PEDOT doped with PSS.
[0076] The solid electrolyte layer containing a conductive polymer can be formed, for example, by impregnating a porous body (anode body) having a dielectric layer formed on its surface with a first treatment liquid containing a monomer (or oligomer), and then polymerizing the monomer (or oligomer) by electrolytic polymerization or chemical polymerization. In the case of chemical polymerization, the first treatment liquid contains, for example, a monomer (or oligomer), an oxidizing agent, and a solvent (or dispersion medium). Examples of the monomer include 3,4-ethylenedioxythiophene (EDOT) and pyrrole. The first treatment liquid may contain a dopant.
[0077] Alternatively, the solid electrolyte layer may be formed by impregnating a porous body (anode body) having a dielectric layer formed on its surface with a treatment liquid containing a conductive polymer, and drying the treatment liquid. The treatment liquid contains, for example, a conductive polymer, a solvent (or a dispersion medium), and, if necessary, a dopant.
[0078] (others) The capacitor element may include a cathode layer covering at least a portion of the solid electrolyte layer. The electrolytic capacitor may include an anode lead terminal and a cathode lead terminal electrically connected to the capacitor element, and an exterior resin arranged around the capacitor element. The cathode lead terminal is connected to the cathode part via a conductive member. The anode lead terminal is connected to an end of the anode wire protruding from the porous body. The shape, size, etc. of the capacitor element are not particularly limited, and may be a known capacitor element or a capacitor element having a similar configuration.
[0079] (cathode layer) The cathode layer may include a carbon layer formed on the solid electrolyte layer and a metal paste layer formed on the carbon layer. The carbon layer may be formed of a conductive carbon material such as graphite and a resin. The metal paste layer may be formed of metal particles (e.g., silver particles) and a resin, for example, a known silver paste.
[0080] (Conductive material) The cathode layer is connected to the connection portion of the cathode lead terminal by a conductive member. That is, the cathode layer (cathode portion) is electrically connected to the cathode lead terminal. The conductive member is made of a material having electrical conductivity. The conductive member may be formed using a material containing metal particles (e.g., silver particles) and a resin, and may be formed using, for example, a known metal paste (e.g., silver paste). The conductive member is formed by heating the metal paste. The conductive member may be made of a plurality of conductive layers of different types.
[0081] (Exterior resin) The exterior resin is disposed around the capacitor element so that the capacitor element is not exposed on the surface of the electrolytic capacitor. Furthermore, the exterior resin insulates the anode lead terminal and the cathode lead terminal. The exterior resin may be a known exterior resin used for electrolytic capacitors. For example, the exterior resin may be formed using an insulating resin material used for sealing the capacitor element. The exterior resin may be formed by placing the capacitor element in a mold, and introducing an uncured thermosetting resin and a filler into the mold by a transfer molding method, a compression molding method, or the like, and curing the resin.
[0082] Examples of the exterior resin include epoxy resin, phenolic resin, silicone resin, melamine resin, urea resin, alkyd resin, polyurethane, polyimide, unsaturated polyester, etc. The exterior resin may contain substances other than resin (such as inorganic filler).
[0083] (Cathode lead terminal) A part of the cathode lead terminal is exposed from the exterior resin and used as a cathode external terminal. The material of the cathode lead terminal may be any material that can be used as a material of a cathode lead terminal of an electrolytic capacitor. For example, a known material of a cathode lead terminal used in an electrolytic capacitor may be used. The cathode lead terminal may be formed by processing a metal sheet (including a metal plate and a metal foil) made of a metal (copper, copper alloy, etc.) by a known metal processing method.
[0084] (Anode lead terminal) A part of the anode lead terminal is exposed from the exterior resin and used as an anode external terminal. The material of the anode lead terminal may be any material that can be used as a material of an anode lead terminal of an electrolytic capacitor. For example, a known material of an anode lead terminal used in an electrolytic capacitor may be used. The anode lead terminal may be formed by processing a metal sheet (including a metal plate and a metal foil) made of a metal (copper, copper alloy, etc.) by a known metal processing method.
[0085] 4 is a cross-sectional view showing a schematic example of the electrolytic capacitor according to the present embodiment, but the electrolytic capacitor according to the present embodiment is not limited to this.
[0086] Electrolytic capacitor 20 includes capacitor element 10, exterior resin 11 that seals capacitor element 10, and anode lead terminal 12 and cathode lead terminal 13 that are electrically connected to capacitor element 10. Anode lead terminal 12 and cathode lead terminal 13 are each partially exposed from exterior resin 11. Anode lead terminal 12 and cathode lead terminal 13 are partially covered by exterior resin 11 together with capacitor element 10.
[0087] Capacitor element 10 includes an anode body 1, a solid electrolyte layer 2 formed on the anode body 1, and a cathode layer 3 formed on the solid electrolyte layer 2. Anode body 1 includes a porous body 4 containing a valve metal, and a dielectric layer 5 covering the porous body 4. Dielectric layer 5 is formed so as to cover the outer surface of porous body 4 and the inner wall surfaces of the pores.
[0088] The porous body 4 has a substantially rectangular parallelepiped shape and has six side surfaces. A part of the anode wire 6 extends from one side surface of the porous body 4. That is, the anode wire 6 has a first portion 6a embedded in the porous body 4 from one side surface of the porous body 4, and a second portion 6b extending from the one side surface of the porous body 4. The second portion 6b is joined to an anode lead terminal 12 by welding or the like.
[0089] The solid electrolyte layer 2 is formed so as to cover at least a portion of the dielectric layer 5. The solid electrolyte layer 2 fills the pores of the porous body 4 (anode body 1). The solid electrolyte layer 2 is formed so as to cover the outer surface S of the porous body 4 and the inner wall surfaces of the pores via the dielectric layer 5.
[0090] The cathode layer 3 is formed so as to cover the surface of the solid electrolyte layer 2. The cathode layer 3 has a carbon layer 3a formed so as to cover the solid electrolyte layer 2, and a metal paste layer 3b formed on the surface of the carbon layer 3a. The cathode lead terminal 13 is joined to the cathode layer 3 (metal paste layer 3b) via a conductive member 8. The carbon layer 3a contains a conductive carbon material such as graphite and a resin. The metal paste layer 3b contains, for example, metal particles (e.g., silver) and a resin. The configuration of the cathode layer 3 is not limited to this configuration. The cathode layer 3 may have any configuration as long as it has a current collecting function.
[0091] Additional Notes The above description of the embodiments discloses the following techniques. (Technology 1) A composite powder used for producing a porous body included in an anode body of an electrolytic capacitor, The composite powder includes a raw material powder containing a valve action metal, and an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and polymers) attached to the surface of particles of the raw material powder, The composite powder, wherein the melting point of the aliphatic carboxylic acid compound is 35°C or higher. (Technology 2) The composite powder according to technical item 1, wherein the melting point of the aliphatic carboxylic acid compound is 35°C or higher and 120°C or lower. (Technology 3) 3. The composite powder according to claim 1 or 2, wherein the boiling point of the aliphatic carboxylic acid compound is 400° C. or lower. (Technology 4) The composite powder according to any one of techniques 1 to 3, wherein the solubility of the aliphatic carboxylic acid compound in 100 g of a solvent at 20° C. is 20 g or more, and the solvent is ethanol, isopropanol, or butyl acetate. (Technology 5) 5. The composite powder according to any one of Techniques 1 to 4, wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of lauric acid, tridecylic acid, myristic acid, and pentadecylic acid. (Technology 6) The composite powder according to any one of Techniques 1 to 5, wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of crotonic acid, elaidic acid, vaccenic acid, nervonic acid, eleostearic acid, and glutaric acid. (Technology 7) The composite powder according to any one of Techniques 1 to 6, wherein the content of the aliphatic carboxylic acid compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder. (Technology 8) The composite powder according to any one of Techniques 1 to 7, wherein the anode body includes the porous body containing the valve metal, and a dielectric layer covering a surface of the porous body. (Technology 9) A method for producing a composite powder used for producing a porous body included in an anode body of an electrolytic capacitor, comprising the steps of: preparing a raw material powder including a valve metal; A step of preparing a carboxylic acid solution containing an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and polymers) having a melting point of 35° C. or higher and a solvent; adding the carboxylic acid solution to the raw material powder while stirring the raw material powder to obtain the raw material powder in a wet state; and drying the wet raw material powder while stirring to remove the solvent, thereby obtaining a composite powder. The composite powder comprises the raw material powder and the aliphatic carboxylic acid compound adhered to surfaces of particles of the raw material powder. (Technology 10) The method for producing a composite powder according to claim 9, wherein the melting point of the aliphatic carboxylic acid compound is 35°C or higher and 120°C or lower. (Technology 11) 11. The method for producing a composite powder according to claim 9 or 10, wherein the boiling point of the aliphatic carboxylic acid compound is 400° C. or lower. (Technology 12) 12. The method for producing a composite powder according to any one of techniques 9 to 11, wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of lauric acid, tridecylic acid, myristic acid, and pentadecylic acid. (Technology 13) The method for producing a composite powder according to any one of techniques 9 to 12, wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of crotonic acid, elaidic acid, vaccenic acid, nervonic acid, eleostearic acid, and glutaric acid. (Technology 14) The method for producing a composite powder according to any one of Techniques 9 to 13, wherein the content of the aliphatic carboxylic acid compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder. (Technology 15) 15. The method for producing a composite powder according to any one of Techniques 9 to 14, wherein the amount of the carboxylic acid solution added is 5 mass % or more and 20 mass % or less per 100 mass parts of the raw material powder. (Technology 16) 16. The method for producing a composite powder according to any one of Techniques 9 to 15, wherein the solvent includes at least one selected from the group consisting of ethanol, isopropanol, and butyl acetate. (Technology 17) 17. The method for producing a composite powder according to any one of claims 9 to 16, wherein the anode body comprises the porous body containing the valve metal and a dielectric layer covering a surface of the porous body. (Technology 18) A step of preparing a composite powder including a raw material powder containing a valve action metal and an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and polymers) attached to the surface of particles of the raw material powder; A step of filling the composite powder into a predetermined molding die and compressing the composite powder to obtain a molded body; removing the aliphatic carboxylic acid compound contained in the molded body; sintering the molded body from which the aliphatic carboxylic acid compound has been removed to obtain a porous body; forming a dielectric layer on the surface of the porous body to obtain an anode body; Including, The method for producing an anode body for an electrolytic capacitor, wherein the aliphatic carboxylic acid compound has a melting point of 35° C. or higher. (Technology 19) The method for producing an anode body for an electrolytic capacitor according to claim 18, wherein the melting point of the aliphatic carboxylic acid compound is 35° C. or more and 120° C. or less. (Technology 20) 20. The method for producing an anode for an electrolytic capacitor according to claim 18 or 19, wherein the boiling point of the aliphatic carboxylic acid compound is 400° C. or lower. (Technology 21) The method for producing an anode body for an electrolytic capacitor according to any one of techniques 18 to 20, wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of lauric acid, tridecylic acid, myristic acid, and pentadecylic acid. (Technology 22) The method for producing an anode body for an electrolytic capacitor according to any one of techniques 18 to 21, wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of crotonic acid, elaidic acid, vaccenic acid, nervonic acid, eleostearic acid, and glutaric acid. (Technology 23) 23. The method for producing an anode body for an electrolytic capacitor according to any one of claims 18 to 22, wherein the content of the aliphatic carboxylic acid compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder.
[0092] [Example] Hereinafter, the present disclosure will be specifically described based on examples and comparative examples, but the present disclosure is not limited to the following examples.
[0093] Examples 1 to 10 (Preparation of composite powder) Ta powder (average particle size: 80 μm, CV value: 70 kCV) was prepared as the raw material powder. A carboxylic acid solution containing an aliphatic carboxylic acid compound A (additive) and ethanol (solvent) was prepared as the additive solution. Myristic acid or lauric acid was used as the aliphatic carboxylic acid compound A. Both myristic acid and lauric acid have a melting point in the range of 35 to 120°C, a boiling point of 400°C or less, and a solubility of 20 g or more in 100 g of ethanol.
[0094] The carboxylic acid solution was added to the raw powder while stirring the raw powder, to obtain a wet raw powder (FIG. 1). The amount of aliphatic carboxylic acid compound A added was the value (parts by mass) shown in Table 1 per 100 parts by mass of raw powder. The concentration of the carboxylic acid solution was appropriately adjusted so that the amount of the carboxylic acid solution added was within the range of 5 to 20 parts by mass per 100 parts by mass of raw powder. The wet raw material powder was heated and dried at a temperature of 90° C. or less while stirring to remove the solvent. In this manner, a composite powder (Ta particles having an aliphatic carboxylic acid compound attached to the surface thereof: composite particles) containing the raw material powder and the aliphatic carboxylic acid compound attached to the surface of the raw material powder particles was obtained.
[0095] (Preparation of Molded Body) A specified amount of composite powder was filled into a specified molding die by leveling and weighing (Fig. 2(a)). One end of an anode wire was embedded in the part filled with composite powder (Fig. 2(b)). The composite powder was then pressure molded to obtain a compact (Fig. 2(c)). The outer shape of the compact was a rectangular parallelepiped (0.8 mm x 3.7 mm x 5.2 mm). Ta wire was used as the anode wire.
[0096] (Preparation of sintered body) The aliphatic carboxylic acid compounds contained in the molded body were removed under reduced pressure at 400 to 500°C. Next, the compact from which the aliphatic carboxylic acid compound had been removed was sintered under reduced pressure at 1300 to 1400°C. At this time, the sintering temperature and sintering time were adjusted so that the shrinkage rate was about 10%. In this way, a porous body (Ta sintered body) in which a part of the anode wire was embedded was obtained.
[0097] Comparative Example 1 An acrylic resin solution (solvent: toluene) was prepared as an additive solution instead of a carboxylic acid solution. The amount of acrylic resin added was 1.5 parts by mass per 100 parts by mass of raw material powder. A composite powder was produced, a molded body was produced, and a sintered body was produced in the same manner as in Example 1 except for the above.
[0098] Comparative Example 2 Instead of the carboxylic acid solution, a camphor solution (solvent: methanol) was prepared as an additive solution. The amount of camphor added was 1.5 parts by mass per 100 parts by mass of raw material powder. Other than the above, a composite powder was prepared in the same manner as in Example 1, a molded body was prepared, and a sintered body was prepared.
[0099] Comparative Example 3 A stearic acid solution (solvent: ethanol) was prepared as an additive solution instead of a carboxylic acid solution. The amount of stearic acid added was 0.01 parts by mass per 100 parts by mass of the raw material powder. A composite powder was produced in the same manner as in Example 1 except for the above.
[0100] Comparative Example 4 No additive was used. That is, a green body was produced in the same manner as in Example 1 except that a raw material powder was used instead of a composite powder, and then a sintered body was produced.
[0101] The green bodies and sintered bodies produced in the above examples and comparative examples were evaluated as follows.
[0102] [evaluation] (Rate of non-defective molded products) In order to evaluate the weighing stability of the powder, the yield rate of the molded body was calculated. Specifically, 300 molded bodies were produced using an automatic molding machine, and the masses of the 300 molded bodies were measured. The ratio of the number of molded bodies whose masses were within ±0.5% of the target mass (good products) among the 300 molded bodies was calculated as the yield rate of the molded body. When the weighing stability of the powder is high, the mass variation of the molded body is reduced, and the yield rate of the molded product is increased.
[0103] (Rate of cracks (chips) in molded bodies) One hundred pieces were randomly selected from the molded bodies produced above. The percentage of the number of molded bodies that had cracks (chips) among the 100 molded bodies was calculated as the crack (chip) occurrence rate (%).
[0104] (Carbon content of sintered body) The carbon content (ppm by mass) of the sintered body was determined using about 1 g of the sintered body using a carbon / sulfur analyzer (manufactured by Horiba, Ltd.).
[0105] (LC in liquid) The sintered body with a part of the anode wire embedded therein was subjected to chemical conversion treatment (anodization). The chemical conversion treatment was performed in a 0.02 mass% phosphoric acid aqueous solution at a chemical conversion voltage of 80 V and a temperature of 60°C. A specified voltage of less than 80 V was applied to the sintered body (anode body) after the chemical conversion treatment in the phosphoric acid aqueous solution, and the current value at the time when a specified time had elapsed since the start of the voltage application was obtained as the in-liquid LC (leakage current).
[0106] (Coefficient of variation indicating the variation in the amount of powder filled into the weighing hole) The coefficient of variation, which indicates the variation in the amount of powder filled into the weighing hole, was determined for the composite powders of Examples 4 and 9 and Comparative Example 3. The coefficient of variation was similarly determined for the raw material powder in Comparative Example 4. The weighing stability was evaluated based on the coefficient of variation.
[0107] The weighing stability was evaluated using an evaluation jig set shown in Fig. 5. The evaluation jig set 600 in Fig. 5 includes a filling jig 610, a weighing jig 620, and a metal plate 640, and was configured to assume filling of the composite powder 300 into the weighing hole 420a using the leveling slider 410 in Fig. 2(a).
[0108] Specifically, a hollow cylindrical filling jig 610 (inner diameter 20 mm) made of stainless steel, a plate-shaped weighing jig 620 (thickness 4 mm) made of stainless steel having a weighing hole 620a (diameter 3 mm) with a circular cross section in the center, and a metal plate 640 were prepared. As shown in FIG. 5, the weighing jig 620 was placed on the metal plate 640, and the filling jig 610 was placed on the weighing jig 620. 2 g of powder 700 was poured into the hollow portion 610a of the filling jig 610, and the filling jig 610 was reciprocated three times (in the direction of the arrow shown in FIG. 5) so as to pass through the weighing hole 620a of the weighing jig 620. In this way, the powder 700 was filled into the weighing hole 620a. Next, the powder 700 filled into the weighing hole 620a was taken out and its mass was measured. Such measurements were repeated 10 times. The standard deviation and average value of the 10 measured values were calculated. The coefficient of variation (%) indicating the variation in the amount of powder 700 filled into measuring hole 620a was calculated as (standard deviation / average value)×100. A small coefficient of variation indicates small variation in the amount of powder filled.
[0109] The evaluation results are shown in Table 1. The amounts of additives added in Table 1 are shown per 100 parts by mass of the raw material powder.
[0110] [Table 1]
[0111] In Examples 1 to 10, the yield rate of the molded bodies was high, good weighing stability was obtained for the composite powder, the carbon content of the sintered body was reduced, and LC in the liquid was reduced. When the amount of the aliphatic carboxylic acid compound added was 0.1 parts by mass or less, no cracks (chipping) were observed in the molded bodies (Examples 1 to 7 and 9). When the amount of the aliphatic carboxylic acid compound added was 0.002 parts by mass or more, the yield rate of the molded bodies was higher and the weighing stability was improved (Examples 2 to 10).
[0112] In Comparative Example 1, where the additive was an acrylic resin, a large amount had to be added to ensure weighing stability, resulting in a high carbon content and an increase in LC in the liquid. In Comparative Example 2, where camphor was added to Ta powder with an average particle size of less than 100 μm, weighing stability decreased and molding yield decreased.
[0113] In Comparative Example 3, in which stearic acid was used as an additive, the coefficient of variation indicating the variation in the powder filling amount was smaller than that in Comparative Example 4, in which no additive was added, but the coefficient of variation was larger than that in Examples 4 and 9, in which an aliphatic carboxylic acid compound A was used as an additive. When the additive was stearic acid, its solubility in ethanol and the like was low, and it took time to prepare a stearic acid solution containing ethanol and the like. In addition, when a stearic acid solution containing ethanol and the like was added to the raw material powder contained in the mixing vessel and wet mixing was performed, stearic acid precipitated on the wall of the mixing vessel, causing uneven mixing. When the additive was palmitic acid, uneven mixing also occurred. [Industrial Applicability]
[0114] The composite powder according to the present disclosure is suitable for use in producing a porous body contained in an anode body of an electrolytic capacitor. [Explanation of symbols]
[0115] 1: anode body, 2: solid electrolyte layer, 3: cathode layer, 3a: carbon layer, 3b: metal paste layer, 4: porous body, 5: dielectric layer, 6: anode wire, 6a: first part, 6b: second part, 8: conductive member, 10: capacitor element, 11: exterior resin, 12: anode lead terminal, 13: cathode lead terminal, 20: electrolytic capacitor, 100: raw material powder, 110: mixing vessel, 200: solution of aliphatic carboxylic acid compound A, 300: composite powder, 310: molded body , 410: leveling slider, 420: weighing mold, 430: press mold, 440: lower mold, 450: upper mold, 460: space, 500: equipment, 510: aliphatic carboxylic acid compound A removal furnace, 520: sintering furnace, 530: aliphatic carboxylic acid compound A recovery tank, 540: heat retention piping, 550: vacuum pump, 600: evaluation jig set, 610: filling jig, 610a: hollow portion, 620: weighing jig, 620a: weighing hole, 640: metal plate, 700: powder
Claims
1. A composite powder used for producing a porous body included in an anode body of an electrolytic capacitor, The composite powder includes a raw material powder including a valve metal, and an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and polymers) attached to a surface of a particle of the raw material powder, The composite powder has a melting point of 35° C. or higher.
2. 2. The composite powder according to claim 1, wherein the melting point of the aliphatic carboxylic acid compound is 35°C or higher and 120°C or lower.
3. 2. The composite powder according to claim 1, wherein the boiling point of the aliphatic carboxylic acid compound is 400° C. or lower.
4. The solubility of the aliphatic carboxylic acid compound in 100 g of a solvent at 20° C. is 20 g or more; The composite powder of claim 1 , wherein the solvent is ethanol, isopropanol, or butyl acetate.
5. 2. The composite powder according to claim 1, wherein the aliphatic carboxylic acid compound comprises at least one selected from the group consisting of lauric acid, tridecylic acid, myristic acid, and pentadecylic acid.
6. 2. The composite powder according to claim 1, wherein the aliphatic carboxylic acid compound comprises at least one selected from the group consisting of crotonic acid, elaidic acid, vaccenic acid, nervonic acid, eleostearic acid, and glutaric acid.
7. The composite powder according to claim 1 , wherein a content of the aliphatic carboxylic acid compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder.
8. The composite powder according to claim 1 , wherein the anode body comprises the porous body containing the valve metal, and a dielectric layer covering a surface of the porous body.
9. A method for producing a composite powder used for producing a porous body included in an anode body of an electrolytic capacitor, comprising the steps of: preparing a raw material powder including a valve metal; A step of preparing a carboxylic acid solution containing an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and polymers) having a melting point of 35° C. or higher and a solvent; adding the carboxylic acid solution to the raw material powder while stirring the raw material powder to obtain the raw material powder in a wet state; and drying the wet raw material powder while stirring to remove the solvent, thereby obtaining a composite powder. The composite powder comprises the raw material powder and the aliphatic carboxylic acid compound adhered to surfaces of particles of the raw material powder.
10. The method for producing a composite powder according to claim 9, wherein the melting point of the aliphatic carboxylic acid compound is 35°C or higher and 120°C or lower.
11. The method for producing a composite powder according to claim 9, wherein the boiling point of the aliphatic carboxylic acid compound is 400°C or lower.
12. The method for producing a composite powder according to claim 9 , wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of lauric acid, tridecylic acid, myristic acid, and pentadecylic acid.
13. The method for producing a composite powder according to claim 9, wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of crotonic acid, elaidic acid, vaccenic acid, nervonic acid, eleostearic acid, and glutaric acid.
14. The method for producing a composite powder according to claim 9 , wherein a content of the aliphatic carboxylic acid compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder.
15. 10. The method for producing a composite powder according to claim 9, wherein an added amount of the carboxylic acid solution is 5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the raw material powder.
16. The method for producing a composite powder according to claim 9 , wherein the solvent includes at least one selected from the group consisting of ethanol, isopropanol, and butyl acetate.
17. The method for producing a composite powder according to claim 9 , wherein the anode body comprises the porous body containing the valve metal, and a dielectric layer covering a surface of the porous body.
18. A step of preparing a composite powder including a raw material powder containing a valve metal and an aliphatic carboxylic acid compound (excluding stearic acid, palmitic acid, and polymers) attached to the surface of particles of the raw material powder; A step of filling the composite powder into a predetermined molding die and compressing the composite powder to obtain a molded body; removing the aliphatic carboxylic acid compound contained in the molded body; sintering the molded body from which the aliphatic carboxylic acid compound has been removed to obtain a porous body; forming a dielectric layer on the surface of the porous body to obtain an anode body; Including, The method for producing an anode body for an electrolytic capacitor, wherein the aliphatic carboxylic acid compound has a melting point of 35° C. or higher.
19. 19. The method for producing an anode body for an electrolytic capacitor according to claim 18, wherein the aliphatic carboxylic acid compound has a melting point of 35°C or higher and 120°C or lower.
20. 19. The method for producing an anode body for an electrolytic capacitor according to claim 18, wherein the aliphatic carboxylic acid compound has a boiling point of 400° C. or lower.
21. 19. The method for producing an anode body for an electrolytic capacitor according to claim 18, wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of lauric acid, tridecylic acid, myristic acid, and pentadecylic acid.
22. 19. The method for producing an anode body for an electrolytic capacitor according to claim 18, wherein the aliphatic carboxylic acid compound includes at least one selected from the group consisting of crotonic acid, elaidic acid, vaccenic acid, nervonic acid, eleostearic acid, and glutaric acid.
23. 19. The method for producing an anode body for an electrolytic capacitor according to claim 18, wherein a content of the aliphatic carboxylic acid compound in the composite powder is 0.002 parts by mass or more and 0.1 parts by mass or less per 100 parts by mass of the raw material powder.
Citation Information
Patent Citations
Method for producing powder metallurgical compact without binder contamination and compact produced by the method
JP2003509583A
Manufacturing method of element for solid electrolytic capacitors
JP2007273710A
Sintering method for tantalum capacitor anode block
JP2013135211A
Tantalum powder, anode and capacitor containing the same, and methods for producing the same
JP2020500260A
solid electrolytic capacitor
JP2022533161A